Logotherapy and Existential Analysis Proceedings of the Viktor Frankl Institute Vienna, Volume 1 - Batthyány, Alexander (Logotherapy and Existential Analysis: Proceedings of the Viktor Frankl Institute Vienna, 2016)
This landmark volume introduces the new series of proceedings from the Viktor Frankl Institute, dedicated to preserving the past, disseminating the present, and anticipating the future of Franklian existential psychology and psychotherapy, i.e. logotherapy and existentialanalysis . Wide-ranging contents keep readers abreast of current ideas, findings, and developments in the field while also presenting rarely-seen selections from Frankl's work. Established contributors report on new applications of existential therapies in specific (OCD, cancer, end-of-life issues) and universal (the search for meaning) contexts as well as intriguing possibilities for opening up dialogue with other schools of psychology. And this initial offering establishes the tenor of the series by presenting varied materials across the field, including: Archival and unpublished articles and lectures by Frankl. Peer-reviewed studies on logotherapy process, measures, and research. New case studies using logotherapy and existential analysis in diverse settings. Papers advocating cross-disciplinary collaboration. Philosophical applications of existential psychology. Critical reviews of logotherapy-related books. Volume 1 of Logotherapy and Existential Analysis will attract a wide audience, including psychologists (clinical, social, personality, positive), psychotherapists of different schools, psychiatrists in private practice, and researchers in these fields. Practitioners in counseling, pastoral psychology, coaching, and medical care will also welcome this new source of ideas and inspiration. .